3D analysis of railway induced vibrations on skew girder bridges including ballast track–bridge interaction effects. (15th March 2023) - Sánchez-Quesada, J.C.; Romero, A.; Galvín, P.; Moliner, E.; Martínez-Rodrigo, M.D.
Abstract: This work is devoted to the analysis of the vibratory response of High-Speed (HS) multi-track railway bridges composed by simply-supported spans. In particular, it aims to investigate the influence of three geometrical aspects usually disregarded in numerical models used to evaluate the Serviceability Limit State of traffic safety in such structures: (i) the deck obliquity, (ii) the presence and correct execution of transverse diaphragms at the supports, and (iii) the number of successive simply-supported spans weakly coupled through the ballast track layer. The influence of these aspects is analysed from the correlation of a detailed numerical model and experimental measurements on an in-service High Speed (HS) multi-track railway bridge. From the reference model, a set of variants accounting for different levels of deck obliquity and diaphragm configurations are envisaged and the maximum transverse acceleration over the platform is determined under railway excitation. The analysis is extended to bridges with an increasing number of successive spans. Special attention is paid to the particular location of the maximum response and to the participation of modes different from the longitudinal bending one. Finally, a numerical–experimental comparison of the bridge response under two train passages is presented for the straight and oblique models, and the response adjustment along with the actual bridge performance are assessed. Highlights: 3D FE model railway bridge updated from experimental data using Genetic Algorithms. Railway bridge catalogue defined from reference case. Sensitivity analysis on deck obliquity, diaphragm configuration and number of spans. Influence of the participation of 3D modes (torsion, transverse bending modes). Numerical–experimental comparison under operating conditions.